PENGARUH LEVERAGE, UKURAN PERUSAHAAN, DAN KUALITAS AUDIT TERHADAP MANAJEMEN LABA (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2008-2013) - FUADILLAH, DZULKIFLI (Jurnal Akuntansi AKUNESA, 2016)
ABSTRACT                Earnings management assumed appear and performed by the manager or the compilers of financial statements in the financial reporting process of a company because they expect a benefit from such action. Earnings management as a phenomenon influenced by various factors that are driving the emergence of the phenomenon. Problems agency (Agency Theory) has attracted great attention from researchers in the field of financial accounting. The inconsistency of the results of previous studies motivate this research to be able to determine the effect of leverage, company size, and audit quality for earnings management. The population in this study are all companies included in the classification of manufacturing industries that have go public company and its shares are listed on the Indonesia Stock Exchange from 2008-2013. The sampling technique used was purposive sampling. Results showed variable leverage significant effect for earnings management. The same thing happened to the variable firm size and quality of the audit that showed a significant effect for earnings management. Keywords : Leverage , Company Size , Audit Quality , Earning Management